Exercise-related pain without clear structural injury – clinical implications for general practice - Pietrasz, Michał (Quality in Sport, 2026)
Background Exercise-related pain is a common reason for consultation among physically active individuals in general practice. In a substantial proportion of cases, pain occurs in the absence of clear structural abnormalities on clinical examination or imaging. Evidence from systematic reviews indicates that morphological findings often poorly correlate with pain severity, creating diagnostic and therapeutic challenges in primary care. Aim The aim of this narrative review was to summarize current evidence on exercise-related pain without clear structural injury and to discuss its clinical implications for general practitioners, with particular emphasis on evidence-based diagnostic reasoning and management strategies. Results Available evidence suggests that exercise-related pain without structural injury may result from load-related mechanisms, impaired neuromuscular control, myofascial pain syndromes, and altered pain modulation, including peripheral and central sensitization. Overreliance on imaging may lead to overdiagnosis of incidental findings and unnecessary interventions. Effective clinical management requires careful clinical assessment, identification of red flag symptoms, patient education, load modification, and a gradual return to physical activity rather than routine diagnostic escalation. Conclusion Exercise-related pain without clear structural injury represents a significant clinical issue in general practice. An evidence-based approach that prioritizes functional assessment, limits unnecessary imaging, and emphasizes patient education and load management may improve clinical outcomes and reduce overt medicalization.